Asyneuma corymbosum (Campanulaceae), a new species from Central Anatolia - Ertuğrul, Tuğba; Aytaç, Zeki̇; Fi̇şne, Ahter (Phytotaxa, 2025)
A new species, Asyneuma corymbosum Aytaç & T. Ertuğrul, has been identified in gypsum soils and arid sandy streambeds of Central Anatolia, Türkiye. Morphologically, the species is closely related to A. rigidum (Willd.) Grossh., but can be distinguished by its pedicellate, usually solitary flowers, as well as by its longer calyx and corolla. While the inflorescence is spicate in many Asyneuma taxa, it is corymbose in the newly described species. A detailed morphological description, diagnostic characters, pollen micromorphology and an identification key are provided. Additionally, its IUCN Red List category and the mapping of the geographical distribution of A. corymbosum and A. rigidum were included.